2017
DOI: 10.1007/s00122-017-2869-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a Phytophthora-resistance gene RpsWY in soybean (Glycine max L.) by high-throughput genome-wide sequencing

Abstract: Key messageUsing a combination of phenotypic screening, genetic and statistical analyses, and high-throughput genome-wide sequencing, we have finely mapped a dominant Phytophthora resistance gene in soybean cultivar Wayao.Abstract Phytophthora root rot (PRR) caused by Phytophthora sojae is one of the most important soil-borne diseases in many soybean-production regions in the world. Identification of resistant gene(s) and incorporating them into elite varieties are an effective way for breeding to prevent soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 74 publications
(152 reference statements)
0
53
0
1
Order By: Relevance
“…The bars flank the candidate region of the QTL for each year and the arrows point at the peaks of the corresponding QTL for each year The nearest maker to the peak position of the LOD distribution in the QTL in the progeny population of NIL147-87 confirmed the qWT_Gm03-containing interval and excluded genomic region downstream of Gm03_3517250_A/C. Previously, a locus (Rps1) conferring resistance to Phytophthora root rot caused by Phytophthora sojae was mapped near the qWT_Gm03 region (Cheng et al, 2017;Gao & Bhattacharyya, 2008). Based on the fine-mapping results, this resistance locus is excluded from the candidate region of qWT_Gm03 (Figure 4).…”
Section: Fine Mapping Narrowed the Candidate Region For Qwt_gm03mentioning
confidence: 88%
“…The bars flank the candidate region of the QTL for each year and the arrows point at the peaks of the corresponding QTL for each year The nearest maker to the peak position of the LOD distribution in the QTL in the progeny population of NIL147-87 confirmed the qWT_Gm03-containing interval and excluded genomic region downstream of Gm03_3517250_A/C. Previously, a locus (Rps1) conferring resistance to Phytophthora root rot caused by Phytophthora sojae was mapped near the qWT_Gm03 region (Cheng et al, 2017;Gao & Bhattacharyya, 2008). Based on the fine-mapping results, this resistance locus is excluded from the candidate region of qWT_Gm03 (Figure 4).…”
Section: Fine Mapping Narrowed the Candidate Region For Qwt_gm03mentioning
confidence: 88%
“…Previous studies have identified 17 known Rps genes (alleles) and mapped them to chromosome 3 before RpsGZ, including five alleles of Rps1 (Rps1a, 1b, 1c, 1d, 1 k) [23,24,38,57,58], Rps7 [23], Rps9 [29], RpsYu25 [25], an Rps gene in Waseshiroge [26], RpsYD29 [27], an Rps gene in E00003 soybean within the Rps1 k interval [30], RpsHC18 [10], RpsQ [13], RpsHN [14], RpsX [9], RpsWY [31], and RpsUN1 [28]. Nevertheless, the positional relationships of these Rps genes had not been confirmed, and some of the mapping intervals for these Rps genes overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…RpsQ, RpsX and an unnamed Rps gene in Wascshiroge and E00003 soybean were mapped to chromosome 3 [7,9,10,13,14,[22][23][24][25][26][27][28][29][30][31]. Rps3 (including three alleles, Rps3a, Rps3b and Rps3c) and RpsSN10 were mapped to chromosome 13, which is linked with Rps8 [6,22,32,33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic resistance is considered the most effective strategy for preventing or reducing the impact of Phytophthora diseases [4,7].Soybean-breeding programs have relied on resistance conferred by single, dominantly inherited Resistance to Phytophthora sojae (Rps)-genes. More than 30 Rps-genes/alleles have been mapped (S1 Table) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The effectiveness of Rps-mediated resistance is limited as these genes only confer immunity towards specific races of P. sojae.…”
mentioning
confidence: 99%